2018
DOI: 10.1007/s00268-018-4669-8
|View full text |Cite|
|
Sign up to set email alerts
|

Differences in Characteristics and Outcome of Patients with Penetrating Injuries in the USA and the Netherlands: A Multi‐institutional Comparison

Abstract: IntroductionThe incidence and nature of penetrating injuries differ between countries. The aim of this study was to analyze characteristics and clinical outcomes of patients with penetrating injuries treated at urban Level-1 trauma centers in the USA (USTC) and the Netherlands (NLTC).MethodsIn this retrospective cohort study, 1331 adult patients (470 from five NLTC and 861 from three USTC) with truncal penetrating injuries admitted between July 2011 and December 2014 were included. In-hospital mortality was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 42 publications
0
22
0
2
Order By: Relevance
“…Blunt injuries were common in our study population, especially in SII. This contrasts with studies from level 1 trauma centers in Western settings where penetrating injuries especially gunshots were more common [22]. In addition to the differences in geographical, cultural and religious backgrounds in the Middle Eastern settings, factors such as urbanization, crime rates, and legislation concerning rearm use could contribute to these existing variations.…”
Section: Discussionmentioning
confidence: 76%
“…Blunt injuries were common in our study population, especially in SII. This contrasts with studies from level 1 trauma centers in Western settings where penetrating injuries especially gunshots were more common [22]. In addition to the differences in geographical, cultural and religious backgrounds in the Middle Eastern settings, factors such as urbanization, crime rates, and legislation concerning rearm use could contribute to these existing variations.…”
Section: Discussionmentioning
confidence: 76%
“…Blunt injuries were common in our study population, especially SII. This contrasts with studies from level 1 trauma centers in Western settings where penetrating injuries especially gunshots were more common [22]. In addition to the differences in geographical, cultural and religious backgrounds in the Middle Eastern settings, factors such as urbanization, crime rates, and legislation concerning rearm use could contribute to these existing variations.…”
Section: Discussionmentioning
confidence: 76%
“…In addition to the differences in geographical, cultural and religious backgrounds in the Middle Eastern settings, factors such as urbanization, crime rates, and legislation concerning rearm use could contribute to these existing variations. Dijkink et al, demonstrated that the proportion of admitted patients with gunshot wounds was almost twice as high in level 1 trauma centers in the United States when compared to level 1 trauma centers in Netherlands, even though the geographical areas in both countries had comparable urbanization and violence crime rates [22].…”
Section: Discussionmentioning
confidence: 99%
“…Another confounder is the trauma mechanism. While in Europe most patients suffer from blunt injuries, penetrating injuries are leading in the United States [29]. Fractures of extremities are a well-known risk factor for venous thromboembolism.…”
Section: Discussionmentioning
confidence: 99%